Experiences of Non-ICU Physicians Redeployment in ICU during COVID-19 - Ahmed F. Mady, Mohammad Al Odat, Omer Alsayed Ramadan, Waqas Mahmood, Rafah Alyousef, Mada Alzahrani, Lojain Abdul Aziz Alshehri, Mohamed Abuhamdah, Basheer Abdel Rahman, Huda A Mhawish, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: During the COVID-19 pandemic, enormous pressure on health care services resulted in a significant shift of work force from different departments of the hospital to the intensive care unit. Objective: To study the impact of redeployment on doctors and to focus on the factors affecting their satisfaction levels. Study Design: Cross-sectional study Place and Duration of Study: Riyadh First Health from 1st April 2021 to 30th September 2021. Methods: Sixty-six respondents were included. Results: Most physicians (59.1%) had no choice before being redeployed to the ICU. The proportion of happy and very happy doctors was 45.5%. A total of seven participants felt very unhappy when they were deployed to the ICU, six of them had no choice and only one had the option to redeploy. Prior to redeploy to the ICU, 37 (56.1%) doctors received orientation, among them 54.05% found it useful. Thirteen participants indicated that they were unclear about their role and 8 (61.5%) of them did not attend the orientation course. 68.2% of doctors worked more than 36 hours a week and 63.6% complained that the number of hours was greater than that of the previous department. 69.7% of doctors found their deployment useful for patient care, while 22.7% were neutral. 62.1 % doctors felt the deployment was beneficial for them and 59.1% felt satisfaction in fulfilling their role and 27.3% were neutral. Forty two (50%) were satisfied with their ICU redeployment and 33.3 % was neutral. Conclusion: By opting few measures, satisfaction levels of redeployed doctors can be boosted. This includes adequate administrative support, a well-organized orientation that clarifies the role of physicians and helps to elevate their morale. Before redeployment physicians should be given a choice so that they can freely join the ICU.